History of western philosophy and its connection with political and social circumstances from the earliest times to the present day - Russell, Bertrand 1872-1970 (George Allen and Unwin Ltd, 1961)
Nearly forty years since its first publication, A History of Western Philosophy remains unchallenged as the ultimate introduction to its subject, while claiming classic status in its own right. It is the bestselling philosophy book of the twentieth century and one of the most important philosophical works of all time. This compact and affordable paperback edition makes this comprehensive and brilliantly written text readily available for a new generation of readers.